Precision sports medicine: The future of advancing health and performance in youth and beyond - Montalvo, A. M.; Tse-Dinh, Y.-C.; Liu, Y.; Swartzon, M.; Hechtman, K. S.; Myer, G. D. (Strength and Conditioning Journal, 2017)
The emerging field of precision medicine emphasizes an individualized approach to prevention, diagnosis, and treatment of disease. Using information from an individual's genetics, environment and lifestyle, epigenetics, and other fields in precision medicine, practitioners can maximize resources by targeting pathology and human performance on the molecular level. However, practitioners may not be aware of topics within this field. Therefore, the purpose of this review is to introduce basic concepts in precision medicine to highlight their potential application to sports medicine and performance enhancement. This review provides practical suggestions for implementation of some currently available precision medicine concepts in sport.